USING INTEGRATED MARKETING COMMUNICATION IN INCREASING CONSUMER INTEREST - Arifa, Arifa; Asfah, Indrawaty; Amin, Fatimah Hidayahni; Susanto, Ashabul Kahfi; Jaya, Muhammad Fahri (Universitas Negeri Makassar, 2024)
This study aimed to analyze the use of Integrated Marketing Communication in increasing consumer interest at PT Antavaya Tour and Travel Makassar. This study used a qualitative approach with a case study design. It analyzed the language functions used by staff PT. Antavaya Tour and Travel Makassar, with reference to the list of language function put forward by Amin (2014) and Halliday (1973). The study also analyzed the impact of using Integrated Marketing Communication in attracting consumer interest. Data were collected through observation, interviews and documentation. The language functions found in increasing consumer interest are asking questions, persuading, informing, asking for confirmation, inviting, explaining, and summarizing. The findings from this study show that the impact of good use of Integrated Marketing Communication such as advertising, sales promotion, public relations, personal selling and direct marketing contributes positively to increasing consumer interest. Implementation of Integrated Marketing Communications has a big influence on sales and increases consumer interest.